Protocol for a Case-Control Study to Investigate the Association of Pellagra With Isoniazid Exposure During Tuberculosis Preventive Treatment Scale-Up in Malawi - Nabity, Scott A.; Mponda, Kelvin; Gutreuter, Steve; Surie, Diya; Williams, Anne; Sharma, Andrea J.; Schnaubelt, Elizabeth R.; Marshall, Rebekah E.; Kirking, Hannah L.; Zimba, Suzgo B.; Sunguti, Joram L.; Chisuwo, Laphiod; et al. (Frontiers in Public Health, 2020)
Background: Pellagra is caused by niacin (vitamin B3) deficiency and manifested by a distinctive dermatitis. Isoniazid is critical for treating tuberculosis globally and is a component of most regimens to prevent tuberculosis. Isoniazid may contribute to pellagra by disrupting intracellular niacin synthesis. In 2017, Malawian clinicians recognized a high incidence of pellagra-like rashes after scale-up of isoniazid preventive treatment (IPT) to people living with HIV (PLHIV). This increase in pellagra incidence among PLHIV coincided with a seasonal period of sustained food insecurity in the region, which obscured epidemiological interpretations. Although isoniazid has been implicated as a secondary cause of pellagra for decades, no hypothesis-driven epidemiological study has assessed this relationship in a population exposed to isoniazid. We developed this case-control protocol to assess the association between large-scale isoniazid distribution and pellagra in Malawi. Methods: We measure the relative odds of having pellagra among isoniazid-exposed people compared to those without exposure while controlling for other pellagra risk factors. Secondary aims include measuring time from isoniazid initiation to onset of dermatitis, comparing niacin metabolites 1-methylnicotinamide (1-MN) and l-methyl-2-pyridone-5-carboxamide (2-PYR) in urine as a proxy for total body niacin status among subpopulations, and describing clinical outcomes after 30-day multi-B vitamin (containing 300 mg nicotinamide daily) therapy and isoniazid cessation (if exposed). We aim to enroll 197 participants with pellagra and 788 age- and sex-matched controls (1:4 ratio) presenting at 3 dermatology clinics. Four randomly selected community clinics within 3–25 km of designated dermatology clinics will refer persons with pellagra-like symptoms to one of the study enrollment sites for diagnosis. Trained study dermatologists will conduct a detailed exposure questionnaire and perform anthropometric measurements. A subset of enrollees will provide a casual urine specimen for niacin metabolites quantification and/or point-of-care isoniazid detection to confirm whether participants recently ingested isoniazid. We will use conditional logistic regression, matching age and sex, to estimate odds ratios for the primary study aim. Discussion: The results of this study will inform the programmatic scale-up of isoniazid-containing regimens to prevent tuberculosis.